2022
DOI: 10.1111/jam.15333
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum HG20 attenuates II type collagen-induced rheumatoid arthritis in rats via anti-inflammatory and inhibition of apoptosis

Abstract: Aims: This study aimed to explore the therapeutic effects of Lactiplantibacillus plantarum HG20 (HG20) on collagen-induced arthritis (CIA) rats and its mechanism. Methods and Results: CIA rats were established by injecting bovine type II collagen for 7 days, and treated by intragastric administration HG20 for 21 days. The foot palm temperature and arthritis score were measured once a week. The pathological changes in the knee joint were observed by hematoxylin and eosin staining.The levels of cytokines were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Indeed, in recent years, an increasing amount of research has shown that intervention with probiotics has a positive effect on the treatment of RA . Administration of Lactobacillus plantarum HG20 in collagen-induced arthritis (CIA) rats significantly reduced joint swelling and downregulated inflammatory and apoptotic pathways of splenic cells . The administration of Bifidobacterium breve CCFM1078 was shown to repair the intestinal barrier of CIA rats, reduce LPS translocation from the intestine, and alleviate inflammation in the spleen via the TLR4-MyD88 pathway .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in recent years, an increasing amount of research has shown that intervention with probiotics has a positive effect on the treatment of RA . Administration of Lactobacillus plantarum HG20 in collagen-induced arthritis (CIA) rats significantly reduced joint swelling and downregulated inflammatory and apoptotic pathways of splenic cells . The administration of Bifidobacterium breve CCFM1078 was shown to repair the intestinal barrier of CIA rats, reduce LPS translocation from the intestine, and alleviate inflammation in the spleen via the TLR4-MyD88 pathway .…”
Section: Introductionmentioning
confidence: 99%
“…11 Administration of Lactobacillus plantarum HG20 in collagen-induced arthritis (CIA) rats significantly reduced joint swelling and downregulated inflammatory and apoptotic pathways of splenic cells. 12 The administration of Bifidobacterium breve CCFM1078 was shown to repair the intestinal barrier of CIA rats, reduce LPS translocation from the intestine, and alleviate inflammation in the spleen via the TLR4-MyD88 pathway. 13 In RA patients, the administration of the probiotic mixture Lactobacillus acidophilus La-14, Lactobacillus casei Lc-11, Lactococcus lactis Ll-23, Bifidobacterium lactis Bl-04, and Bifidobacterium bifidum Bb-06 significantly reduced the white blood cell count, TNF-α, and IL-6 levels in the plasma.…”
Section: Introductionmentioning
confidence: 99%